Contribution to the study on chemical constituents of Hedyotis crassifolia L., (Rubiaceae) - Huu, Bui Chi; Phi Phung, Nguyen Kim (Vietnam Journal of Chemistry, 2014)
Six compounds as ursolic acid (1); 3β-hydroxyurs-11-ene-28(13)-lactone (2); 3α,13β-dihydroxyurs-11-ene-28-oic acid (3); oleanolic acid (4); 3β-D-glucopyranosyl-β-sitosterol (5)and 3β,6β-dihydroxyolean-12-ene-28-oic acid (6) were isolated from Hedyotis crassifolia L. (Rubiaceae). Among them, (3) was a new triterpen.